2006
DOI: 10.1016/j.neuroimage.2006.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Support MEG imaging

Abstract: In this paper, we present a novel approach to imaging sparse and focal neural current sources from MEG (magnetoencephalography) data. Using the framework of Tikhonov regularization theory, we introduce a new stabilizer that uses the concept of controlled support to incorporate a priori assumptions about the area occupied by focal sources. The paper discusses the underlying Tikhonov theory and its relationship to a Bayesian formulation which in turn allows us to interpret and better understand other related alg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…whose solution is the Minimum Support Estimate (MSE) [20]. In [6,5,7], the authors have shown that, in the context of traditional image processing, the corresponding penalty is related to the Perona-Malik functional [23].…”
Section: Hypermodels: Mce Minimum P and Beyondmentioning
confidence: 99%
See 1 more Smart Citation
“…whose solution is the Minimum Support Estimate (MSE) [20]. In [6,5,7], the authors have shown that, in the context of traditional image processing, the corresponding penalty is related to the Perona-Malik functional [23].…”
Section: Hypermodels: Mce Minimum P and Beyondmentioning
confidence: 99%
“…In this work, we construct a conditionally Gaussian hierarchical parametric model that has the computational advantages of Gaussian prior models but leads to a rich class of MAP estimators that have the desirable qualitative properties of numerous commonly used non-Gaussian models. Using the conditional normality, we construct a fast, efficient and simple MAP estimation algorithm, and show that with proper choices of the few model parameters, the algorithm can be interpreted as a fixed point iteration for solving the minimum norm estimate, the minimum current estimate and, more generally, the minimum p estimate, while with a different choice, the algorithm approximates the minimum support estimate (MSE) [20]. Hence, our approach puts these methods in a unified framework.…”
Section: Introductionmentioning
confidence: 99%
“…A special example consists in algorithms performing smooth and sparse estimations in separate steps (Liu et al, 2005 ; Palmero-Soler et al, 2007 ) to explicit combining models as the sum of L1 and L2 penalty functions while using iterative algorithms to solve it (Nagarajan et al, 2006 ; Valdés-Sosa et al, 2009 ; Tian and Li, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge this is the first time that the use of probabilistic Bayesian PCA for data covariance estimation has been demonstrated in the context of MEG beamforming. A related probabilistic regularised estimation of the covariance matrix has been used previously as part of a method for analysing MEG and EEG data (Nagarajan et al (2007, 2006)). In particular, in Nagarajan et al (2007) they propose an interesting generative modelling approach that uses baseline periods to learn noise components (or “interferences”), thereby allowing them to partition noise from signal components in the time period of interest.…”
Section: Discussionmentioning
confidence: 99%